Advanced biological treatment processes for industrial wastewaters : principles and applications - Cervantes, Francisco J., ....-; Pavlostathis, Spyros G., ....-; Van Haandel, Adrianus C., ....- (London : IWA, 2006)
Advanced Biological Treatment Processes for Industrial Wastewaters provides unique information relative to both the principles and applications of biological wastewater treatment systems for industrial effluents. Case studies document the application of biological wastewater treatment systems in different industrial sectors such as chemical, petrochemical, food-processing, mining, textile and fermentation. With more than 70 tables, 100 figures, 200 equations and several illustrations, the book provides a broad and deep understanding of the main aspects to consider during the design and operation of industrial wastewater treatment plants. Students, researchers and practitioners dealing with the design and application of biological systems for industrial wastewater treatment will find this book invaluable.
Keywords: Afvalwaterzuivering